2015
DOI: 10.1063/1.4915917
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Lennard-Jones nanodroplets: From near melting to deeply supercooled

Abstract: We carry out molecular dynamics (MD) and Monte Carlo (MC) simulations to characterize nucleation in liquid clusters of 600 Lennard-Jones particles over a broad range of temperatures. We use the formalism of mean first-passage times to determine the rate and find that Classical Nucleation Theory (CNT) predicts the rate quite well, even when employing simple modelling of crystallite shape, chemical potential, surface tension and particle attachment rate, down to the temperature where the droplet loses metastabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 67 publications
3
22
2
Order By: Relevance
“…Comparing the growth rate obtained by the MD simulations, i.e., di 1/3 c /dt = 0.04σ/τ , with Eq. (2), we obtain where we used i = (4π/3)a 3 n, h = 0.58ε [42], T 0.5ε/k, T m = 0.69ε/k [38], and n = 0.92σ −3 [29]. The diffusion coefficient of the liquid at T 0.5ε/k obtained in [44] was approximately 0.01, which is smaller than our calculated value.…”
Section: Crystal Growthcontrasting
confidence: 48%
See 4 more Smart Citations
“…Comparing the growth rate obtained by the MD simulations, i.e., di 1/3 c /dt = 0.04σ/τ , with Eq. (2), we obtain where we used i = (4π/3)a 3 n, h = 0.58ε [42], T 0.5ε/k, T m = 0.69ε/k [38], and n = 0.92σ −3 [29]. The diffusion coefficient of the liquid at T 0.5ε/k obtained in [44] was approximately 0.01, which is smaller than our calculated value.…”
Section: Crystal Growthcontrasting
confidence: 48%
“…A study of crystal nucleation in bulk LJ liquid by [39] reported the values of γ = (0.28-0.3)εσ −2 for T 0.45ε/k. In [42], the nucleation rates were obtained by MD simulations of 600 LJ molecules with a potential cutoff radius of 15 σ , and γ was evaluated from the fitting of the obtained nucleation rates as γ = 0.13εσ −2 at T = (0.35-0.485)ε/k, which is smaller than that obtained in our calculation. The reasons for the difference between our calculation of γ and that of [42] may be considered.…”
Section: Rewritten Asmentioning
confidence: 68%
See 3 more Smart Citations